2018
DOI: 10.1039/c7ta10218f
|View full text |Cite
|
Sign up to set email alerts
|

Nickel metal–organic framework implanted on graphene and incubated to be ultrasmall nickel phosphide nanocrystals acts as a highly efficient water splitting electrocatalyst

Abstract: Ultrasmall Ni2P/rGO was synthesized using template-confinement strategy of MOFs and served as a highly efficient electrocatalyst for overall water splitting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
78
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 171 publications
(79 citation statements)
references
References 81 publications
1
78
0
Order By: Relevance
“…[18][19][20] In the past two decades, MOFs have been shown to have variousa pplicationss uch as for gas storage, gas separation, sensors, proton conduction and optoelectronic devices. [40][41][42] Recently,h etero-NiFe bimetallic MOF was shown as ar obust electrode materialf or electrochemical OER. [27] Besides being highly crystalline, MOFs are easily recyclable and robust under numerous chemical and physicalc onditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20] In the past two decades, MOFs have been shown to have variousa pplicationss uch as for gas storage, gas separation, sensors, proton conduction and optoelectronic devices. [40][41][42] Recently,h etero-NiFe bimetallic MOF was shown as ar obust electrode materialf or electrochemical OER. [27] Besides being highly crystalline, MOFs are easily recyclable and robust under numerous chemical and physicalc onditions.…”
Section: Introductionmentioning
confidence: 99%
“…[38,39] Ni(OH) 2 has been explored widely as an activee lectrocatalyst for OER activity.N evertheless, Ni-MOFsa re found to be better substitutes for Ni(OH) 2 owing to their high surface areas and tunable structures. [40][41][42] Recently,h etero-NiFe bimetallic MOF was shown as ar obust electrode materialf or electrochemical OER. [43] Further,t wo-dimensionaln ickel phthalocyanine-based MOF wass hown to exhibit remarkable catalytic activity in the alkaline medium.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene has been widely studied and explored because of its unique structural and physicochemical properties of stable structure and long cycling life . As a result, Tan et al reported a N‐doped graphene/Fe–Fe 3 C (NG/Fe–Fe 3 C) nanocomposite in 2014, which was prepared by a facile one‐pot method using MIL‐100 (Fe) (as shown in Figure b).…”
Section: Batteriesmentioning
confidence: 99%
“…Therefore, a well‐established effective technology, water electrolysis is used to yield clean hydrogen energy . However, the practical hydrogen evolution activity is limited because of the sluggish reaction kinetics of both HER and OER, which require high overpotentials and show low efficiency . Hence, it is of great importance to decrease the overpotentials of water splitting by using electrocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…[10] However, the practical hydrogen evolution activity is limited because of the sluggish reaction kinetics of both HER and OER, which require high overpotentials and show low efficiency. [10][11][12] Hence, it is of great importance to decrease the overpotentials of water splitting by using electrocatalysts. Up to now, for the HER and OER, the most excellent electrocatalysts are still noble metals, such as platinum, platinumbased materials, iridium, and ruthenium oxides.…”
Section: Introductionmentioning
confidence: 99%